Comparison of Normal saline, Activated Charcoal and Intravenous Lipid Emulsion in a Rat Model of Colchicine Overdose: Experimental Study - Çelikmen, Mustafa Ferudun; Sarikaya, Sezgin; Özüçelik, Doğaç Niyazi; Canbolat, Fadime; Sümer, Engin; Keleş, Elif Çiğdem; Çelikmen, Deniz Sema Maktav (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim The aim of this study is to investigate the effects of Normal Saline (NS), Activated Charcoal (AC) and Intravenous Lipid Emulsion (ILE) in colchicine poisonings that resulted in death. Study Design The research is an experimental study carried out in a medical school animal laboratory. Materials and Methods 24 female Sprague-Dawley rats were divided into 4 equal groups. After giving Colchicine (1 mg/kg, PO) to all animals, different treatments (NS, AC, ILE) were given to 3 groups. Group 4 was not treated. Colchicine blood samples (0.8 mL) were taken from the vena jugularis externa at 4, 8 and 24 hr and evaluated by liquid chromatography. Results While the blood colchicine level decreased in all groups at 24 hr, the highest decrease was observed in the AC group. Compared to the 4th hr, blood colchicine levels at 8 hr decreased by 15.49% in the NS group, 64.55% in the AC group and 34.56% in the ILE group. Blood colchicine levels at 24 hr decreased by 66.1% in the NS group, 73.12% in the AC group, 37.73% in the ILE group and 59.17% in the untreated group compared to the 8th hr. Conclusion AC administration is very effective in lowering blood colchicine levels. ILE can be used with NS and AC as an early treatment option for colchicine overdoses. However, further studies are needed for more effective methods in the treatment of colchicine overdose.
Keywords: Colchicine overdose; intoxication; Normal saline; Activated charcoal; intravenous lipid emulsion